Analisa Peran Dan Fungsi Pelabuhan Perikanan Nusantara Brondong Terhadap Peningkatan Ekonomi Maritim Di Kabupaten Lamongan - Muhammad Fadlan Rizqi Wahyudi; Minto Basuki (Jurnal Universal Technic, 2023)
This study aims to analyze the role and function of the Archipelago Brondong Fishing Port for improving the maritime economy in Lamongan Regency. Among them are the factors that affect fishermen's income, the role of PPN Brondong in the maritime sector, as well as the potential and realization of the maritime economy of PPN Brondong in Lamongan Regency. The analytical method used is descriptive method through a qualitative approach, in its application using primary and secondary data from the research results that have been analyzed. The author uses a triangulation technique to be able to validate data and draw conclusions about the role and function of the Archipelago Brondong Fishing Port for improving the maritime economy in Lamongan Regency. The results of the study prove that the role and function of the Archipelago Brondong Fishing Port have an important influence on the potential for adding added value to the maritime economy in Lamongan Regency.